Functional Capacity, Lipid Profile, and Associated Factors in Older Adults Living in Urban and Rural Areas - Francieli Cristina Comelli Medeiros; Clodoaldo Antônio De Sá; Eduardo Ottobeli Chielle; Fátima Ferretti; Rosana Amora Ascari; Gabriela Peretro; Vanessa da Silva (Corralo) (Journal of Aging Research)
This study aimed to analyze the relationship between sociodemographic and lifestyle variables, functional strength, aerobic capacity, and lipid profile of older adults living in urban and rural areas. For this purpose, 208 older adults were evaluated (132 living in rural areas and 73 living in urban areas). Sociodemographic data were collected, and functional strength, aerobic capacity, and lipid profile of older adults living in the southern region of Brazil were evaluated. Only total cholesterol and LDL cholesterol were associated with place of residence (p<0.05), and living in the countryside was associated with low aerobic capacity (p=0.010). The use of medication (OR = 3.01; p=0.012) and smoking (OR = 0.30; p=0.027) were the only variables that explained aerobic performance, regardless of place of residence. In conclusion, place of residence is not a factor that, alone or in combination with other conditions, affects the functional performance or lipid profile of the older adult population.